Stereoselective synthesis of 4-hydroxymethyl-1, 3-oxazolidin-2-one derivatives from novel 2-hydroxymethylaziridines. Issue 17 (2nd September 2018) - Ouerfelli, Oussema; Tabarki, Mohamed Ali; Pytkowicz, Julien; Arfaoui, Youssef; Brigaud, Thierry; Besbes, Rafâa
Abstract: A stereoselective and simple method for the synthesis of trans -2-hydroxymethyl- N -alkyl-1, 3-oxazolidin-2-ones is described. The synthesis involved the reduction of trans -aziridine-2-carboxylates with LiAlH4, followed by a ring opening and a cyclization reaction in the presence of methyl chloroformate to afford the target trans -oxazolidinones in completely regio- and stereoselective process. A plausible reaction mechanism has been proposed involving an SN 1 pathway and a detailed computational study of this mechanistic process has been carried out using theoretical calculations. Graphical Abstract: